Pembingkaian Isu Politik di TikTok dan Pengaruhnya Terhadap Opini Publik Pemilu Malaysia 2022 - Jazil, Alfan Khoirul; Lila, Annisa Rahma; Alamsyah, Tegar; Sari, Septiana; Nisa, Pia Khoirotun (Universitas Pahlawan Tuanku Tambusai, 2025)
The transformation of digital media has changed the way people receive and shape political information, especially through the TikTok platform which is now a popular political campaign medium among the younger generation. This study aims to examine the form of framing of political content on TikTok during the 2022 Malaysian Election and its influence on the formation of public opinion. With a qualitative approach and using Robert N. Entman's framing model, this study analyzes how political issues are constructed by creators and political parties on TikTok. The results show that TikTok is not only a tool for political mobilization, but also an arena for narrative battles that significantly influence the orientation of young voters. These findings emphasize the importance of media literacy and digital ethics in the current digital democratic landscape.